Elaboración de una guía de actividades deportivas, recreativas que permita emplear la práctica deportiva como estrategia metodológica en los estudiantes del 2do de bachillerato del colegio “José Gabriel Teran Varea” parroquia Guaytacama, cantón Latacunga, durante el año lectivo 2011-2012 - Armas Mena, Oscar Andrés (2014)
The Physical Culture has taken a significant step in the Ecuadorian education, however it is necessary to increase the number of methodological activities for the strengthening of the programd teachers, based on this principle a research was developed with the objective to make the design of a guide of sporting, recreational for the students of the College "José Gabriel Terán Varea" in the parish Guaytacama, city of Latacunga. The present study included a series of surveys and interviews with managers, teachers, parents and students of the mentioned school. As a result it was demonstrated the importance of sport by applying the proposed guidance, where he got 100% of teachers of Physical Culture approved the proposed ideas, engaging in the implementation of methodological guidelines to support the educational process....